2009
DOI: 10.1002/hipo.20570
|View full text |Cite
|
Sign up to set email alerts
|

Spatio‐temporal dynamics of theta oscillations in hippocampal–entorhinal slices

Abstract: Theta oscillations (4-12 Hz) are associated with learning and memory and are found in the hippocampus and the entorhinal cortex (EC). The spatio-temporal organization of rhythmic activity in the hippocampal-EC complex was investigated in vitro. The voltage sensitive absorption dye NK3630 was used to record the changes in aggregated membrane voltage simultaneously from the neuronal networks involved. Oscillatory activity at 7.0 Hz (range, 5.8-8.2) was induced in the slice with the muscarinic agonist carbachol (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 77 publications
(85 reference statements)
5
13
0
Order By: Relevance
“…Many years of research conducted with the use of models of HPC slice preparations have allowed us to determine the specific role of the cholinergic (Kazmierska et al, 2012;Konopacki et al, 1987Konopacki et al, , 2006Konopacki, 1998;Kowalczyk et al, 2001) and GABAergic systems (Gołębiewski et al, 1996;Konopacki and Gołębiewski, 1993;Konopacki et al, 1997) in providing the adequate level of neuronal excitation necessary for theta to appear. Our findings are supported by a large body of data from other laboratories, in which carbachol-induced theta rhythm in hippocampal slices Cappaert et al, 2009;Fellous and Sejnowski, 2000;McQuiston, 2010;Natsume and Kometani, 1999) and urethanized rats (Kinney et al, 1998;Leung and Péloquin, 2010;Monmaur et al, 1997;Yoder and Pang, 2005) were observed. Interestingly, Bland (2008) proposed that cholinergic projections provide a steady tonic excitatory afferent drive for HPC theta-related cells while GABAergic projections act to reduce the overall level of inhibition by inhibiting hippocampal GABAergic interneurons (Cappaert et al, 2009;Smythe et al, 1992).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…Many years of research conducted with the use of models of HPC slice preparations have allowed us to determine the specific role of the cholinergic (Kazmierska et al, 2012;Konopacki et al, 1987Konopacki et al, , 2006Konopacki, 1998;Kowalczyk et al, 2001) and GABAergic systems (Gołębiewski et al, 1996;Konopacki and Gołębiewski, 1993;Konopacki et al, 1997) in providing the adequate level of neuronal excitation necessary for theta to appear. Our findings are supported by a large body of data from other laboratories, in which carbachol-induced theta rhythm in hippocampal slices Cappaert et al, 2009;Fellous and Sejnowski, 2000;McQuiston, 2010;Natsume and Kometani, 1999) and urethanized rats (Kinney et al, 1998;Leung and Péloquin, 2010;Monmaur et al, 1997;Yoder and Pang, 2005) were observed. Interestingly, Bland (2008) proposed that cholinergic projections provide a steady tonic excitatory afferent drive for HPC theta-related cells while GABAergic projections act to reduce the overall level of inhibition by inhibiting hippocampal GABAergic interneurons (Cappaert et al, 2009;Smythe et al, 1992).…”
Section: Introductionsupporting
confidence: 90%
“…Our findings are supported by a large body of data from other laboratories, in which carbachol-induced theta rhythm in hippocampal slices Cappaert et al, 2009;Fellous and Sejnowski, 2000;McQuiston, 2010;Natsume and Kometani, 1999) and urethanized rats (Kinney et al, 1998;Leung and Péloquin, 2010;Monmaur et al, 1997;Yoder and Pang, 2005) were observed. Interestingly, Bland (2008) proposed that cholinergic projections provide a steady tonic excitatory afferent drive for HPC theta-related cells while GABAergic projections act to reduce the overall level of inhibition by inhibiting hippocampal GABAergic interneurons (Cappaert et al, 2009;Smythe et al, 1992).…”
Section: Introductionsupporting
confidence: 90%
“…The initial demonstration of atropine‐sensitive theta rhythm recorded in brain slices was performed by Konopacki et al (). Since then, theta oscillations and synchrony have been successfully studied in in vitro preparations of several brain structures, including neocortex (Lukatch and MacIver, ; Bao and Wu, ), entorhinal cortex (Konopacki and Gołębiewski, ; Cappaert et al, ), and finally HPC (Heynen and Bilkey, ; Huerta and Lisman, ; Fellous and Sejnowski, ; Konopacki et al, ; Kowalczyk et al, , ). Slice preparations of PHa were previously used in electrophysiological studies of the MB and PH single neurons (Greene et al, ; Alonso and Llinás, ; Llinás and Alonso, ), thermosensitivity of the PH and MB neurons (Dean and Boulant, ), neuroendocrinological studies (Zisapel et al, ), and investigations concerning the anesthetics modulation of hypothalamic functions (Kushikata et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The hope is to facilitate endogenous oscillations at these frequencies, but the lack of experimental evidence for this makes the study of the cellular and network effects of stimulation on these rhythms particularly important.There are in vitro preparations that generate beta rhythms (Shimono et al, 2000) and thalamo-cortical spindles (Von Krosigk et al, 1993; Tancredi et al, 2000), while to our knowledge, there are currently no in vitro models of alpha oscillations. Theta oscillations (Cappaert et al, 2009; Goutagny et al, 2009) and ripples (Behrens et al, 2005; Nimmrich et al, 2005) can also be pharmacologically induced. Rodent brain slice preparations are obviously a poor model for human brain rhythms; nevertheless they have proven to be a useful tool to study the cellular substrate of tACS particularly because stimulation may be applied in a controlled setting and specific interactions between networks of oscillating neurons can be systematically probed.…”
Section: Future Directionsmentioning
confidence: 99%